The intracerebral hemorrhage blood transcriptome in humans differs from the ischemic stroke and vascular risk factor control blood transcriptomes. Issue 9 (September 2019) - Stamova, Boryana; Ander, Bradley P; Jickling, Glen; Hamade, Farah; Durocher, Marc; Zhan, Xinhua; Liu, Da Zhi; Cheng, Xiyuan; Hull, Heather; Yee, Alan; Ng, Kwan; Shroff, Natasha; et al.
Understanding how the blood transcriptome of human intracerebral hemorrhage (ICH) differs from ischemic stroke (IS) and matched controls (CTRL) will improve understanding of immune and coagulation pathways in both disorders. This study examined RNA from 99 human whole-blood samples using GeneChip® HTA 2.0 arrays to assess differentially expressed transcripts of alternatively spliced genes between ICH, IS and CTRL. We used a mixed regression model with FDR-corrected p (Dx) < 0.2 and p  < 0.005 and |FC| > 1.2 for individual comparisons. For time-dependent analyses, subjects were divided into four time-points: 0(CTRL), <24 h, 24–48 h, >48 h; 489 transcripts were differentially expressed between ICH and CTRL, and 63 between IS and CTRL. ICH had differentially expressed T-cell receptor and CD36 genes, and iNOS, TLR, macrophage, and T-helper pathways. IS had more non-coding RNA. ICH and IS both had angiogenesis, CTLA4 in T lymphocytes, CD28 in T helper cells, NFAT regulation of immune response, and glucocorticoid receptor signaling pathways. Self-organizing maps revealed 4357 transcripts changing expression over time in ICH, and 1136 in IS. Understanding ICH and IS transcriptomes will be useful for biomarker development, treatment and prevention strategies, and for evaluating how well animal models recapitulate human ICH and IS.